PENAKSIRAN NILAI EKONOMI REHABILITASI KAWASAN MANGROVE DI DESA MOJO KECAMATAN ULUJAMI KABUPATEN PEMALANG - , YUNISA ROSMAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Mangrove rehabilitation is cost center that is not a priority government program. The economic and ecological benefit externality are not counted because it does not have market price. There should be comprehensive assessment of the benefits and costs of mangrove rehabilitation, so that economic efficiency can be achieved. These purposes research are (1) to know estimated direct value (wood value) and indirect value (biological, retaining abrasion and retaining intrusion value) with mangrove rehabilitation at the coastal of Mojo village, (2) and to know estimated economic value from mangrove rehabilitation by using ENPV, EBCR and EIRR parameter. The method used in this research are concepts with and without, the total economic value, change in productivity to assess biological benefits and retaining abrasion, and cost saving to assess retaining intrusion. Results quantifying the benefits with mangrove rehabilitation area of 26,13 ha obtained a total value of economic amounting to Rp 241.288.075,00 /ha/year which consists of direct use value in the form of mangrove wood value of Rp 3.331.466,00 /ha/year and indirect use value of Rp 237.956.609,00 /ha/year, calculated from the biological benefits as spawning and feeding ground of Rp 20.714.951,00 /ha/year